Pengaruh Pengangguran terhadap tingkat kesehatan di Kabupaten Gowa Sulawesi Selatan - Lestari, Novita Dian; Warda, Warda; Achsanuddin, Nur (Universitas Teuku Umar, 2025)
This study examines the influence of poverty on poverty levels in Gowa Regency, South Sulawesi. The goal is to analyze how poverty reduction affects poverty. Using a quantitative approach, this study utilizes time series data from 2014 to 2024 collected through observation and documentation. The data were analyzed using simple linear regression using SPSS version 30. The results consistently show that poverty has a significant positive effect on poverty levels in Gowa Regency. This finding indicates that increasing poverty contributes to increasing poverty. The main implication is the need for urgent public policy interventions to create jobs and reduce poverty rates as a crucial strategy for sustainable poverty alleviation.Keywords: Unemployment, Poverty